Towards Cross-Border Fisheries Management: An Analysis of Fleet Structures and Species-Specific Regulatory Measures in the Aegean Sea - DERELİ, HAKKI and ÜNAL, VAHDET and ULMAN, AYLIN and GIOVOS, IOANNIS and TOSUNOĞLU, ZAFER and PRODROMITIS, GEORGE and MOUTOPOULOS, DIMITRIOS K. (Mediterranean Marine Science, 2024)
Intrinsic differences in the applied management measures of shared stocks in transboundary waters inhibit the ability of either state to benefit from such measures, as one state may benefit in lieu of the other, thus reducing the efficacy of both. This study compares for the first time the fleet structure, specific management measures applied to species-specific regulations for commercial fishing, species listed in official monitoring schemes, and protected taxa between Greece and Türkiye for the Aegean Sea. A comparative analysis utilizing the official data was sourced from both countries. Large-scale Greek and Turkish fishing fleets have been modernized within the last 30 years (1991-2021). Greek and Turkish large-scale fishing fleets included smaller trawlers with lower tonnage and slightly higher engine horsepower, while purse seines of both states included larger vessels with higher horsepower and tonnage. This indicates that the fishing pressure on the demersal resources in the Aegean Sea has partially decreased, but the fishing pressure on pelagic resources has increased despite the decrease in the number of vessels. Only 11 out of 74 minimum conservation reference sizes (MCRS) are sufficiently set above the Lm50 sizes they should be based on, whereas 18 species need reproductive studies, and 22 are set below the Lm50, and could benefit from an increase. The application of specific closed seasons for commercial species was used by both states with the intent to protect the reproductive periods of some stocks. However, several of these closure periods did not fully or even partially cover the spawning periods of the respective species. Species-specific closures were applied to 13 species in Greece and 23 species in Türkiye, with only two fish species (Xiphias gladius and Thunnus thynnus) listed for both countries. Only 14 species (out of 34 protected by Greece and 46 by Türkiye) are protected by both states, most of which are listed as critically endangered by the International Union for Conservation of Nature and Natural Resources (IUCN). Harmonization of fisheries management measures currently does not align between the two neighbouring states, and the General Fisheries Commission of the Mediterranean is the competent authority that would be able to restructure such measures, especially as Türkiye has been aligning their measures with that of the EU for the accession process. This contribution highlights the clear differences between Greece and Türkiye, and provides advice for developing a unified management regime for the Aegean Sea.